Perlindungan Hukum Bagi Kreditur Dalam Financial Technology Berbasis Peer to Peer Lending di Indonesia - Radefi, Alicia (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
One form of information technology advances in the financial or financial sector is the presence of technology-based financial services actors or known as financial technology (fintech). The National Digital Research Centre (NDRC) suggests that fintech is one of the developments in the field of finance that realize financial transactions that are more effective, efficient, and modern. Peer to peer lending (P2PL) is a form of fintech that is widely used today. The outbreak of the COVID-19 pandemic in all parts of the world, including Indonesia, has caused P2PL as a type of fintech service to become more menggurita in people's lives. The outbreak of the pandemic made the community's economy paralyzed. Fintech services that offer convenience can be a solution to problems that occur. No need for guarantees or collateral as well as fairly easy requirements such as ID cards, tin, and also selfies with ID cards can have bad implications for creditors if one day there is a default on the loan agreement by the debtor. On the part of the creditor attached a very high risk such as the occurrence of default because the debtor does not carry out its obligations or achievements that can harm the creditor. Defaults and defaults by debtors have the potential to occur.. From the data of the p2pl fintech development statistical report in October 2020, it also stated that the increasing percentage of defaults by debtors to creditors. This study aims to determine the legality and mechanism of Peer to Peer Lending as a type of Financial technology and know the legal protection for creditors in P2pl-based Financial Technology. The research used is normative legal research. Data collection techniques in this study is done by means of literature studies and document studies of legal materials related to this study legal protection for creditors is absolutely necessary in order to create a legal certainty and a sense of security for the creditors themselves.